Edukasi Kewirausahaan Sebagai Upaya Menanamkan Jiwa Wirausaha Sejak Dini dalam Mendukung Program MKBM Asistensi Mengajar di Salama Kelurahan Na’e Kota Bima - Kartin Aprianti; Irma Mardian; Muh. Abie Nasution H; Anna Nurul Ike; Alfiana Ayu S; Tria Rosalina; Aulia Rizqi M; Birrul Walidaini (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
One of the programs that is part of the Merdeka Belajar Kampus Merdeka (MBKM) is Teaching Assistance. The Teaching Assistance Program is an activity carried out by students in order to enrich their academic experience, improve their teaching skills, and assist with the learning process at school or college. Through the Teaching Assistance Program by the KKNT-MBKM TEAM at SDN 16 Kota Bima and SDN Integral Lukman Hakim Kota Bima, steps have been taken to provide education related to entrepreneurship.and also its implementation to students with the aim of making them become more creative, innovative, independent, responsible and confident. Providing entrepreneurship socialization and its implementation to students is a process to train their entrepreneurial spirit from an early age in accordance with their creativity and innovation, so that they can increase their potential. The results of this service show that the students involved are starting to show an increase in their understanding of entrepreneurship. They are braver in expressing ideas and more active in learning activitie.